치과의료소비자의 라이프스타일에 의한 병원 만족도 - 박정순; Chung Soon Park; 김진; Jin Kim (Chiwisaeng gwahakoeji, 2009)
The purpose of this study was to examine the relationship between the lifestyle of dental consumers and their hospital satisfaction level in an attempt to lay the foundation for successful dental marketing strategy setting. The subjects in this study were 720 medical consumers who visited dental institutions in Jeolla buk-do province. A survey was conducted from October 1 to December 1, 2006, with self-administered questionnaires. The collected data were analyzed with SPSS(Statistical Package for the Social Science) 12.0 program to find out their lifestyle and hospital satisfaction level. Concerning the impact of lifestyle on satisfaction with dental institutions, lifestyle made a difference to the satisfaction level of the hospital users with promptness and economicality(p < 0.001). As to connections between hospital-reuse intention and satisfaction level, those who were willing to reuse the dental institutions they had visited expressed better satisfaction with promptness(p < 0.05). As for links between health-related lifestyle and hospital satisfaction level, health conscious style, health promoting style health unconscious styles had a statistically significantly positive relationship to hospital satisfaction level, which showed a significant relationship between the three lifestyles and hospital satisfaction level. As for factors affecting reuse of dental institutions, it's found that their intention to reuse the same dental institution they had visited was linked to their satisfaction level with it, what made them choose it and their health-related lifestyle. In the future, more precise and in-depth questionnaires should be developed to analyze the health-related lifestyle of medical consumers. 본 연구는 대상자의 라이프스타일에 따른 병원 만족도 신뢰도를 파악하고 일반특성에 따른 병원 만족도를 분석하여 라이프스타일에 따른 병원 만족도를 파악하였으며, 병원 재이용의 영향요인을 알아보기 위하여 2006년 10월 1일부터 12월 1일까지 전라북도 지역의 구강보건진료기관을 내원하는 의료소비자를 대상으로 자기 기입식으로 응답한 720부 설문지를 사용하였으며, 수집된 자료는 SPSS WIN 12.0 프로그램을 이용하여 분석한 결과 다음과 같은 결론을 얻었다. 1. 연구대상자의 일반적인 특성에 따른 병원만족 요인을 분석한 결과 '신속성' 요인에서는 성별(p < 0.05), 소득(p < 0.05), 연령(p < 0.05)에서 통계적으로 유의한 차이를 보였다. '신뢰성' 요인에서는 주로 이용하는 치과진료기관(p = 0.004)에서 통계적으로 유의한 차이를 보였으며, '접근성' 요인에서는 연령(p < 0.001)에서 통계적으로 유의한 차이를 보였다. '경제성' 요인에서는 연령(p < 0.05)과 주로 이용하는 치과진료기관(p < 0.05) 에서 통계적으로 유의한 차이를 보였으며, '편리성' 요인에서는 주로 이용하는 치과진료기관(p < 0.01)에서 통계적으로 유의한 차이를 보였다. 2. 라이프스타일에 따른 치과진료기관 만족 요인의 차이는 신속성과 경제성 요인에 대해서는 건강라이프스타일에 따라 병원만족 요인을 지각하는 정도가 다르게 나타났으며, 신속성을 지각하는데 있어서 '건강실천형(I)'과 '건강무실천형(II)'간에 통계적으로 유의한 차이를 보였고(p < 0.05). 경제성 요인에서는 '건강실천형(I)'과 '건강무실천형(II)', '건강관심형(III)', '건강무관심형(IV)'간에 유의한 차이를 보였다(p < 0.001). 3. 병원 재이용의사에 따른 만족요인의 차이는 신속성의 경우 재이용의사가 있는 경우가 없는 경우보다 만족정도가 높게 나타났으며, 통계적으로 유의한 차이를 보였다(p < 0.05). 또한 신뢰성에서도 재이용의사가 있는 경우 만족정도가 높게 나타나 통계적으로 유의한 차이를 보였다(p < 0.001). 4. 건강라이프스타일과 병원만족도와의 관계를 살펴보면, 건강관심형, 건강실천형, 건강무관심형에서는 통계적으로 유의적인 정(+)의 관계를 보여 의미 있는 상관관계가 존재하는 것으로 나타났다.